A Household Time-Use and Energy-Consumption Model with Multiple Behavioral Interactions and Zero Consumption. (April 2013) - Yu, Biying; Zhang, Junyi; Fujiwara, Akimasa
This study develops a new household resource allocation model, which incorporates multiple interactions (including the interaction between time use and energy consumption, the interactivity interaction, the inter-end-use interaction, and the intrahousehold interaction) based on multilinear utility functions and endogenously represents zero consumption for both time and energy within the group decision-making modeling framework. This may be the first model in literature to jointly accommodate all these behavioral mechanisms in a unified and consistent modeling framework, especially in the context of time use and energy consumption. The model is estimated using data collected in a household survey in Beijing in 2010. Estimation results reveal that: (1) synergic effects are observed with respect to in-home time use and energy consumption, out-of-home time use across varied activities, and in-home energy consumption from different end uses; (2) competitive relationships are detected between in-home time use and out-of-home energy consumption, out-of-home time use and in-home energy consumption, in-home and out-of-home energy consumption, and time use. These not only support the joint representation for time use and energy consumption behavior but also for the energy consumption behavior of in-home end uses and out-of-home vehicles. Additionally, it is found that the intrahousehold interaction does exist.